2022
DOI: 10.3390/foods11070950
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Response to the SARS-CoV-2 Pandemic: Concern about Ultra-Processed Food Consumption

Abstract: Introduction: There is scientific consistency in the concept of ultra-processed foods (UPFs) as a descriptor of an unhealthy diet. The most recent literature points to troubling evidence that policies adopted to address the SARS-CoV-2 pandemic may have contributed to diverting eating habits toward a poorer diet. Considering the historically unique SARS-CoV-2 pandemic lockdown scenario, and the health burden imposed by UPFs on human health, it is critical to investigate how the epidemic has influenced UPF intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
0
17
0
1
Order By: Relevance
“…This study revealed a high prevalence of mental disorder symptoms, given the high prevalence of symptoms of anxiety and depression in Brazilian adults during the COVID-19 pandemic. This prevalence may be explained by the fear of the disease and its implications for health, uncertainties about the spread of the virus and its treatment, the high mortality rates, and the loss of family members and relatives, in addition to the disruption of daily routines and lifestyles marked by the imposition of restrictive measures characterized by social distance ( 8 ), the restriction of physical and in-person trade ( 43 ), the decrease in physical activity during leisure time and the increase in sedentary behavior ( 44 , 45 ), increased alcohol consumption ( 46 , 47 ), a decreased purchase of fresh foods, and increased impulse buying ( 48 ), especially of ready-to-eat foods with high durability ( 49 , 50 ), characterizing health risk behaviors. Studies have shown that engaging in these behaviors, especially those related to comfort, may be a way for people to manage psychological distress and stressful situations ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed a high prevalence of mental disorder symptoms, given the high prevalence of symptoms of anxiety and depression in Brazilian adults during the COVID-19 pandemic. This prevalence may be explained by the fear of the disease and its implications for health, uncertainties about the spread of the virus and its treatment, the high mortality rates, and the loss of family members and relatives, in addition to the disruption of daily routines and lifestyles marked by the imposition of restrictive measures characterized by social distance ( 8 ), the restriction of physical and in-person trade ( 43 ), the decrease in physical activity during leisure time and the increase in sedentary behavior ( 44 , 45 ), increased alcohol consumption ( 46 , 47 ), a decreased purchase of fresh foods, and increased impulse buying ( 48 ), especially of ready-to-eat foods with high durability ( 49 , 50 ), characterizing health risk behaviors. Studies have shown that engaging in these behaviors, especially those related to comfort, may be a way for people to manage psychological distress and stressful situations ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be associated with the increased time spent at home in addition to the sociocultural tendencies of Jordanians in their associations with eating sweets and snacks, especially in this time period. A study conducted in 2022 in Italy investigating the changes in eating habits also indicated that there is a clear trend in the increasing consumption of ultra-processed foods such as sweets (43). Some of the limitations include the fact that we were not able to independently confirm the data reported both before and after the onset of the pandemic.…”
Section: Discussionmentioning
confidence: 83%
“…In this context, non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in developed countries, exceeding 25% among European adults ( 2 ). The highest prevalence has been reported in the Middle East and South America, reaching 70% in populations with obesity and diabetes ( 3 , 4 ). Individuals with metabolic syndrome or its components are more frequently affected by fatty liver disease, clinically described as a spectrum of liver disease combined with metabolic and cardiovascular disorders ( 5 ).…”
Section: Introductionmentioning
confidence: 99%